2005
DOI: 10.1128/aem.71.10.6267-6275.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic Substance Photodegradation on Bacterial Growth and Respiration in Lake Water

Abstract: This study addresses how humic substance (HS) chemical composition and photoreactivity affect bacterial growth, respiration, and growth efficiency (BGE) in lake water. Aqueous solutions of HSs from diverse aquatic environments representing different dissolved organic matter sources (autochthonous and allochthonous) were exposed to artificial solar UV radiation. These solutions were added to lake water passed through a 0.7-mpore-size filter (containing grazer-free lake bacteria) followed by dark incubation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 65 publications
2
90
0
5
Order By: Relevance
“…For example, Febria et al (2006) found that the production of hydrogen peroxide (H 2 O 2 ) in two delta lakes that were also sampled herein (CON and TK) outpaced the rate of removal during a period of uninterrupted sunshine in 2004, leading to an accumulation of H 2 O 2 within the water columns. Production of ROS during previous studies of DOM photodegradation has been observed to inhibit community-level rates of carbon production (Scully et al 2003;Anesio et al 2005;Glaeser et al 2014) and result in changes in bacterial community composition (Glaeser et al 2010(Glaeser et al , 2014. Further, in a prior study by Lund and Hongve (1994), declines in BA of up to 60% were observed after only an hour when UV-irradiated DOM was mixed with bacteria.…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 97%
See 3 more Smart Citations
“…For example, Febria et al (2006) found that the production of hydrogen peroxide (H 2 O 2 ) in two delta lakes that were also sampled herein (CON and TK) outpaced the rate of removal during a period of uninterrupted sunshine in 2004, leading to an accumulation of H 2 O 2 within the water columns. Production of ROS during previous studies of DOM photodegradation has been observed to inhibit community-level rates of carbon production (Scully et al 2003;Anesio et al 2005;Glaeser et al 2014) and result in changes in bacterial community composition (Glaeser et al 2010(Glaeser et al , 2014. Further, in a prior study by Lund and Hongve (1994), declines in BA of up to 60% were observed after only an hour when UV-irradiated DOM was mixed with bacteria.…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 97%
“…8b), where an initial sharp increase in SBP also suggested that the surviving bacteria were released from a relative shortage of growth substrate. Increased BP and growth have been observed in the presence of irradiated DOM in many freshwater systems (e.g., Anesio et al 2005;Paul et al 2012), including in the circumpolar Arctic (Cory et al 2013;Ward et al 2017), where photochemical oxidation of DOM accounts for the majority of C processing (Cory et al 2014). Prior work in the Mackenzie Delta has shown that lower molecular weight DOM derived from macrophytes supports higher rates of BGE in communities isolated from a variety of habitats (including TK and CON lakes;Tank 2009).…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the combination of initial photochemical degradation of the DOM form smaller molecules and that they are more accessible to microbial degradation. This is also important for the total OM mineralization (Bertilsson and Allard, 1996;Tranvik and Bertilsson, 2001;Anesio et al, 2005). When expanding these findings from short-term incubations over time and space, large seasonal differences in lake OM cycling should be expected in stratified and ice-covered systems where different proportions of the OM are exposed to light during different seasons.…”
Section: Introductionmentioning
confidence: 99%